2011
DOI: 10.1007/s00167-011-1410-7
|View full text |Cite
|
Sign up to set email alerts
|

Classification of trochlear dysplasia as predictor of clinical outcome after trochleoplasty

Abstract: Purpose Sulcus-deepening trochleoplasty restores the trochlear groove in patients with patellofemoral instability and underlying trochlear dysplasia. There are types of dysplasia both with (B and D) and without (A and C) a supratrochlear spur. The aim of this study was to identify influencing factors for the clinical outcome following trochleoplasty. Methods Forty-four knees in 38 patients who underwent trochleoplasty for instability (type A in 9, B in 15, C in 9 and D in 11 knees) were assessed clinically wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
120
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(131 citation statements)
references
References 25 publications
8
120
2
1
Order By: Relevance
“…While all articles defined clear inclusion criteria, only half of them described exclusion criteria [10,15,23,27,29,33,35]. There were different inclusion criteria in most of the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While all articles defined clear inclusion criteria, only half of them described exclusion criteria [10,15,23,27,29,33,35]. There were different inclusion criteria in most of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Fucentese et al [10] have shown superior results in type B and D trochlear dysplasia than in type A and C when treated with trochleoplasty. Some consensus exists on the fact that trochleoplasty cannot be the only solution for all types of patellofemoral instability.…”
Section: Discussionmentioning
confidence: 99%
“…Fucentese et al reviewed 44 knees in 38 patients with patellar instability treated with deepening trochleoplasty and no other procedures performed at that time. A 37% of patients reported no improvement in pain and 8% reported worse pain following surgery than before 60 . There were six cases of recurrent instability and 18% of patients said they would not repeat the surgery 60 .…”
Section: All Authors Contributed To Conception and Design Manuscriptmentioning
confidence: 93%
“…A 37% of patients reported no improvement in pain and 8% reported worse pain following surgery than before 60 . There were six cases of recurrent instability and 18% of patients said they would not repeat the surgery 60 . Fucentese et al concluded that pain relief following trochleoplasty is not predictable but that this procedure does improve stability in most patients.…”
Section: All Authors Contributed To Conception and Design Manuscriptmentioning
confidence: 93%
“…The role of postoperative MR imaging is to assess the resulting femoral groove depth and the lateral femoral inclination. However, 10-30 % of patients may suffer increased pain after intervention, and MR images may show progression of degenerative changes in the femoropatellar joint [ 62 ].…”
Section: Mri Postoperative Findingsmentioning
confidence: 99%